3 ( 3x - 1 ) = 2 ( 3x + 2 ) *com o calculo pfvr*
Soluções para a tarefa
Respondido por
1
Resposta: 3 (3x - 1) = 2 (3x + 2)
9x - 3 = 2 (3x + 2)
9x - 3 = 6x + 4
9× - 3 + 3 = 6x + 4 + 3
9x = 6x + 7
9x - 6x = 6x + 7 - 6x
3x = 7
3x/3 = 7/3
Explicação passo a passo:
Respondido por
1
3*(3x - 1) = 2*(3x + 2)
9x - 3 = 6x + 4
9x - 6x = 4 + 3
3x = 7
x = 7/3
Perguntas interessantes
Contabilidade,
7 meses atrás
Filosofia,
7 meses atrás
Pedagogia,
7 meses atrás
Biologia,
7 meses atrás
Geografia,
7 meses atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás